(untitled) (Scientific journal of the Fergana State University, 2024)
Soft drinks are filling the shelves of grocery stores. Drinks with red tints are of interest. The work proposes a food coloring based on the amaranth plant, which also contains biologically active substances. The dye is made on the basis of Japanese Sophora (Safora), which contains rutin, flavonoids and other biologically active substances.